PENGARUH INDEPENDENSI, KOMPETENSI, DAN PROFESIONALISME TERHADAP KUALITAS AUDIT - MIKHAIL EDWIN NUGRAHA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Great trust of the users of audited financial statements and other services provided by a public accountant requires public accountants to audit the quality attention it generates. This study aims to analyze the effect of independence, competence and professionalism of audit quality. Quality audit is a possibility (joint probability) in which an auditor will discover and report violations of existing clients in the accounting system. The possibility of misstatement the auditor will find depends on the auditor's understanding of the quality (competence), after it reported a misstatement of action depends on the independence of the auditor. High quality audit will produce reliable financial statements as a basis for decision making. In addition, an auditor must comply with applicable laws and regulations and should avoid any actions that could discredit the profession, this is related to the principle of professional behavior of an auditor. Object of this study is the independent auditor in Surabaya. The research data obtained from filling out the questionnaire with the amount of data as many as 47 people respondent of 21 KAP. Sampling technique using a convenience sampling. Analysis of data using a test of validity, reliability test and linear regression. These results indicate that the independence and professionalism does not have a positive significant effect on audit quality, whereas a significant positive effect on the competence of quality audit.